Surgical management of Hawkins type III talar neck fracture through the approach of medial malleolar osteotomy and mini-plate for fixation - Hui Liu; Zhida Chen; Wenrong Zeng; Yuanfei Xiong; Yongzhi Lin; Huacheng Zhong; Jin Wu (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Fractures of the talar neck are relatively uncommon yet current interventions suffer from a high incidence of complications and poor functional outcomes. In the present study, we report a surgical treatment of Hawkins type III talar neck fracture through the approach of medial malleolar osteotomy and mini-plate for fixation and discuss the therapeutic effects after long-term follow-up. Methods From January 2010 to January 2015, 21 patients with 22 fractures were treated using this approach within days of sustaining the injury. Clinical and radiographic data were collected during regular post-operative follow-ups. Health-related quality of life factors were evaluated using visual analogue scale (VAS). Functional outcomes were determined according the Hawkins score and the Ankle-Hind foot Scale of the American Orthopedic Foot and Ankle Society (AOFAS). Present of complications such as arthritis, avascular necrosis (AVN), and malunion were evaluated using radiographs and magnetic resonance imaging (MRI). Anatomical parameters of injured and corresponding uninjured talus were measured and compared using digital three-dimensional (3D) computer model. Results The mean duration of surgery was 65.6 ± 9.7 min. The average blood loss volume of the patients was 29.1 ± 5.7 ml. All the patients except 1 were followed up 18 to 41 months (average 29.6 months). The average VAS score for these patients was 3.2 ± 1.1, and the mean Hawkins score was 11.4 ± 3.4 at the final follow-up visit. The average AOFAS score was 72.8 ± 17.3. Nine patients outcomes were rated as “excellent”, 4 as “good”, 4 as “fair,” and 4 as “poor”. No malunion, screw loosening, plate breakage, or other internal fixation failures were found at final follow-up. Long-term complications included: 1 case of malunion, 5 cases of complete AVN, 8 cases of partial AVN, 13 cases of talocrural arthritis, 14 cases of subtalar arthritis, and 3 cases of talonavicular arthritis. Secondary surgery was performed in 4 cases. The relevant average anatomical data of injured and uninjured talus show no significant difference. Conclusions This surgical treatment we used here resulted in decreased soft tissue trauma, adequate exposure of talar neck, satisfactory performance of daily life activities, and quality of life following surgery and restoration of anatomy of injured talus. However, long-term complications such as arthritis and AVN are still commonly seen.